Characterizing Håkon Mosby Mud Volcano (Barents Sea) cold seep systems by combining ROV-based acoustic data and underwater photogrammetry - Fallati, Luca; Panieri, Giuliana; Argentino, Claudio; Varzi, Andrea Giulia; Bünz, Stefan; Savini, Alessandra (Frontiers in Marine Science, 2023)
Cold-seeps have a unique geo-ecological significance in the deep-sea environment. They impact the variability of present-day submarine sedimentary environments, affecting the evolution of the landscape over time and creating a variety of submarine landforms, one of which is Mud Volcanoes (MVs). MVs form due to the extrusion of mud, fluids, and gas, mainly methane, from deeper sedimentary layers. These natural gas seepage systems could significantly affect climate change and the global carbon cycle. We present a comprehensive method that combines ROV-based multibeam mapping and underwater photogrammetry to enhance the understanding of the physical relationships between geomorphic units characterizing the Håkon Mosby Mud Volcano (HMMV) and the distribution of associated habitats. HMMV is indeed characterized by high thermal and geochemical gradients from its center to the margins resulting in a clear zonation of chemosynthetic communities. Our approach integrates multi-resolutions and multi-sources data acquired using a work-class ROV. The ROV-based microbathymetry data helped to identify the different types of fine-scale submarine landforms in the central part of HMMV. This revealed three distinct geomorphic units, with the central hummocky region being the most complex. To further study this area, ROV images were analyzed using a defined Structure from Motion workflow producing millimetric resolution 2D and 3D models. Object-Based Image Analysis (OBIA), applied on orthomosaics, allowed us to obtain a fine classification of main benthic communities covering a total area of 940m2, including the active seepage area of the hummocky rim. Four major substrate types were identified in these regions: uncovered mud, bacterial mats high-density, bacterial mats low-density, sediments and tubeworms. Their relationship with terrain morphology and seepage activity were investigated at different spatial scales, contributing to a deeper understanding the ecological functioning of cold seep ecosystems in MVs. The applied workflow is proposed as an innovative processing technique for future studies on cold-seep systems. Geomorphic and ecological processes in extreme environments are inherently linked and marked by spatial patterns typifying associated habitats and sedimentary environments. This is poorly investigated in previous studies, leaving a substantial gap in the geomorphological drivers responsible for habitat distribution and extent in cold seep systems.